Effects of Gestational Exposure to Potassium Bromate as Food Additive on Reproductive and Immunological Parameters in Mouse Offspring (Journal of Science and Technology Research, 2024)
Potassium bromate (KBrO3) is used as a food additive because of its high oxidizing characteristics, which have been linked to carcinogenic and mutagenic effects. The study looked into how KBrO3 exposure during gestation affected the growth, reproductive performance, and immune cells of parental mice and their F1 generation. Thirty Swiss Albino mice (Mus musculus) aged 27±3 days were collected from ICDDR'B in Dhaka, with 10 males and 20 females. When the mice reached 45 days of age, they were randomly separated into two groups, each with ten females and five males. Group A mice served as the untreated control, while group B mice were given KBrO3 at 400 mg/liter in drinking water. Body weights were obtained at 2-week intervals. The results revealed that KBrO3 reduced growth in both male and female parental mice. The KBrO3-treated group showed considerably reduced amounts of estradiol, testosterone, and T4 (P